Laboratory studies and preliminary field evaluation of vaccination trials against pasteurellosis in ducks - RAMANATHA, K R (The Indian Journal of Animal Sciences, 2013)
Formalin-inactivated, alum-adsorbed broth bacterin of Pasteurella multocida A: 1 from ducks was tested in laboratory and field trials. An indirect haemagglutination (IHA) test using glutaraldehyde-fixed sheep erythrocytes sensitized with crude capsular polysaccharide was conducted on duck sera for humoral antibody levels. The highest ranges of IHA titres of sera from once and twice vaccinated ducks were, respectively, 80-640 and 1 280-10 240 as aganist 0Â·40 from unvaccinated ducks. The IHA titres were significantly higher (P